2020
DOI: 10.1111/ssqu.12751
|View full text |Cite
|
Sign up to set email alerts
|

“Ain't No Hood Like Motherhood”: The Complexity of Human Milk Donor Identity

Abstract: Objective This article draws on the literature of bodily gifting, the motivations for milk donation, and donor identity to explore human milk donation in the context of nonprofit milk banks. We ask: What are the characteristics of the milk donor identity? Methods We qualitatively analyze written testimonials and images produced by human milk donors during the time of their milk donation. Results We found that milk donors comprised complex identities: the identity of a mother, of a woman, sometimes a recipient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The most common donor experience studied was reasons/ enablers for donation (16,(18)(19)(20)(21)24,26,(30)(31)(32)35,37,39,43) . Common reasons for donation included altruism, having excess milk and avoiding waste (16,18,20,30,32,36,37,43) . Common enablers for donation were being encouraged to donate and receiving information about milk banks from healthcare providers (19)(20)(21)24,(30)(31)(32)35,36,39) .…”
Section: Donor Experiences and Beliefsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common donor experience studied was reasons/ enablers for donation (16,(18)(19)(20)(21)24,26,(30)(31)(32)35,37,39,43) . Common reasons for donation included altruism, having excess milk and avoiding waste (16,18,20,30,32,36,37,43) . Common enablers for donation were being encouraged to donate and receiving information about milk banks from healthcare providers (19)(20)(21)24,(30)(31)(32)35,36,39) .…”
Section: Donor Experiences and Beliefsmentioning
confidence: 99%
“…Major themes: information received about milk banks and perceived approval of family and friends, having excess milk, altruism, empathy, support from family and milk bank USA (18) 2007 87 donors To help others, having excess milk (% not provided) USA (24) 2012 21 donors Major themes: physical and emotional meanings of pumping, finding meaning in perinatal loss, and importance of healthcare providers addressing lactation with bereaved mothers USA (26) 2013 19 donors Major theme: deriving value from the physical and emotional labour of pumping USA (36) 2018 12 donors Major themes: hope of donation helping others, act of donating was nurturing for the donor, importance of support from healthcare staff and desire to share their stories USA (37) 2018 2 donors Major themes: milk donation as a mean of processing perinatal loss and doing something helpful with their milk USA (43) 2020 95 donor testimonials…”
Section: Donor Experiences and Beliefsmentioning
confidence: 99%
See 2 more Smart Citations
“…Donors who engage in bodily gifting often hold identities of helpers, altruists, or generous givers (e.g., Piliavin & Callero, 1991). Studies on milk donation have found that milk donor identity is complex, comprised maternal and female identities (Gribble, 2014; Oreg & Appe, 2020; Palmquist & Doehler, 2014) and at times is influenced by a distinct professional identity of a health care provider (e.g., nurse, physician; Oreg & Appe, 2020).…”
Section: Care Work and Women’s Philanthropymentioning
confidence: 99%